Binary Surfactant–Mediated Tunable Nanotip Growth on Gold Nanoparticles and Applications in Photothermal Catalysis - Mi, Xiaohu; Zhang, Tingting; Zhang, Baobao; Ji, Min; Kang, Bowen; Kang, Chao; Fu, Zhengkun; Zhang, Zhenglong; Zheng, Hairong (Frontiers in Chemistry, 2021)
The plasmonic nanostructures with sharp tips have been widely used for optical signal enhancement due to the strong light confinement ability, which have been widely used for sensing, bioimaging and SERE technique. Gold nanoparticles exhibit a great photothermal conversion efficiency in visible to near infrared region due to the strong light absorption ability, which has largely contributed to the application of photothermal catalysis. The existing method of synthesizing the nanostructures with tips, however, always need the assistance of PVP, thiol compounds and biomolecules, which highly hinders the detected signal due to the stubborn residues. Herein, we proposed an efficient method mediated by binary surfactants to control the nanotips growth on arbitrary surface of the gold nanoparticles, which not only can exclude the influence from surfactants, but also can used for any arbitrary shape of the Au nanostructures. The tip growth process of the Au architectures can be well controlled by the adjusting the ratio of CTAB and CTAC resulting from the contribution of the different attraction ability between Br-/Cl- and Au3+ ions. Furthermore, the SERS and catalytic ability of the synthesized nanoparticles with tips have been evaluated by both electromagnetic simulation and photothermal catalysis experiment (p-nitrobenzenethiol), which shows a grate application potential in SERE technique. This method provides a new strategy for designing plasmonic photothermal nanostructures for the applications of chemical and biological applications.